Influence of biological preparations on the phytosanitary state of soybean seeds - Поспєлова, Г. Д.; Бараболя, О. В.; Морозова, О. О. (Scientific Progress & Innovations, 2018)
Soybean is one of the most demanded legumes in the world of leguminous crops. In recent years, there has been a significant increase in its production in Ukraine. The presence of pathogenic flora on the seed material significantly affects its quality, further development of plants and productivity of the studied crop. The vast majority of researchers offer to disinfect seeds and protect them from soil infection using chemical agents that in their opinion effectively and long-term protect a crop with a minimum negative environmental impact. Modern requirements for the quality of agricultural products focus on the use of environmentally safe plant protection measures, which include the biomethod. The purpose of the research is to investigate the influence of biopreparations on the degree of infection and the species composition of phytopathogens of soybean seeds, the crop quality of the investigated material, the development of plants in the initial stages of organogenesis and their racing properties. As a result of the research, the crop quality of the soybean seeds of Vilshanka crop was determined in 2016 and 2017. The germination energy and laboratory similarity were higher in the seeds of the crop in 2016: 78.3% and 81.8% respectively, the level of infection was 56%. In 2017 it showed a little worse quality, contamination with pathogens was 88.5%. In order to determine the causes of low crop quality of soybean seeds the microscopy of grain with signs of damage was performed. Fungal pathogens and bacterial etiology were detected. It should be noted that the fungal pathogens dominated the samples under study regardless of the harvest year. Their distribution was 85.71% and 85.76 %. Bacterial infections did not exceed 15%, and a certain number of specimens (2016 – 16.42%, and in 2017 – 7.11%) was characterized by a mixed infection. Alternaria was the highest in the soybean affected by the Alternaria genus, reaching 25.3% in 2016, while in 2017 this figure was almost three times smaller – 8.7%. The prevalence of fungi of Fusarium and Botrytis genera in the 2016 harvest was 2.2% and 2.5%, while in 2017, the level of gray rot affected was 1.2%, and the defeat of Fusarium sp. remained at last year level. The species composition of saprophytes in 2016 was represented by fungi of the genera Mucor, Aspergillus, Penicillium. The prevalence ranged from 0.5% (Penicillium sp.) to 7.5% (Mucor sp.). And in 2017 the species of scads of pathogens of secondary infection decreased to two genera Mucor, Aspergillus (3.3% and 1.5% respectively). The next stage of the research was the assessment of the biological activity of fungicidal preparations of chemical and biological origin against detected phytopathogenic microorganisms. As a benchmark, «Maxim XL» fungicide was used, as well as biological products «Phytodoctor» and «Trichodermin» in other cases. In our experiments carried out in 2016 chemical fungicide «Maxim XL» decreased the manifestation of fungal infection in 6.5 times, and in 2017 – 5.9 times compared with the control, while it was not effective against the bacterial infection. In this variant the infection with bacterial pathogens was 4.3–3.2%. In «Trichodermin» and «Phytodoctor» variants, the laboratory similarity was recorded at almost the same level – 85.1% and 85.3%, respectively, while the number of conditionally healthy seedlings was slightly higher with the use of «Trichodermin» – 95.2%, which is 2.3% higher than in the version with «Phytodoctor» (92.9%). «Trichodermin» showed greater effectiveness against fungal etiology, which decreased to 3.3%. «Maxim XL» positively influenced the similarity of the seeds – 93.4%, but was not sufficiently effective against the bacterial flora, the prevalence of which was manifested at 3.8%. It is worth noting that «Maxim XL» actively destroys the fungal pathogenic microflora, which was 2.8%, that is 4.8% less compared to the control. In addition to the evaluating the effectiveness of the drugs studied against the pathogenic flora, we determined their effect on the growth and development of soy sprouts. The analysis of the data shows the positive effect of biofungicides on the development of soybean variety Vilshanka. Thus, the height of the germs for the use of drugs «Trichodermin» and «Phytodoctor» increased in comparison with the control of 8.4 mm and 10.6 mm respectively, while the chemical trainer suppressed this figure by 5.8 mm. A similar trend was observed in the determining the length of the root. Consequently, at the initial stages of the development of soy plants, biopreparations showed a stimulating effect.